Mapping municipal land policies: applications of flexible zoning for densification - Vera Götze; Jean-David Gerber; Mathias Jehling (Buildings & Cities)
Municipalities develop individual land policies and can choose not to apply available planning instruments or to apply them differently than intended. While this strategic action can endanger the effectiveness of public policies, it is rarely considered in large-scale analyses. A new geospatial method is presented that captures such strategic action. Empirical evidence from the Canton of Bern, Switzerland, reveals municipalities’ application of planned unit development (PUD), an instrument potentially allowing for flexible zoning negotiations to promote densification. Detailed zoning and building data from the period 2002–23 are used to examine the variation in PUD application by municipalities and whether they apply it to enable densification. Distinguishing by municipality type (i.e. urban core, small town, suburban, rural or touristic) reveals that PUD application is connected to projects with higher building density, more complex parcel changes and, for urban and suburban municipalities, higher density gains in low-density neighbourhoods. However, rural municipalities seldom apply PUD. New indicators of planning complexity provide an insight into whether municipalities apply instruments to enable densification under difficult circumstances. Practice relevance Many policy instruments are provided for in the law, but it is unclear whether and how they are used in practice by municipalities. Following urban densification objectives, municipalities often struggle to implement planning or housing policy instruments, which target private landowners and developers. Therefore, evaluating how different municipalities apply policy instruments and how this application contributes to reaching stated policy goals is crucial. Therefore, this research explores new ways to capture the effect of policy instruments with spatial analysis. Furthermore, by examining the real-world implementation of PUDs, this research sheds light on possible barriers to PUD application for densification, thereby helping policymakers and urban planners improve the effectiveness of public policies.